The EORTC QLQ-BN20 for assessment of quality of life in patients receiving treatment or prophylaxis for brain metastases: a literature review. (December 2011) - Leung, Andrew; Lien, Karen; Zeng, Liang; Nguyen, Janet; Caissie, Amanda; Culleton, Shaelyn; Holden, Lori; Chow, Edward
Introduction: Brain metastases occur in approximately 20–40% of cancer patients during the course of disease. As treatment for brain metastases is palliative over curative, quality of life (QoL) is emphasized over prolonged survival. The European Organization for Research and Treatment of Cancer (EORTC) QLQ-BN20 is a QoL assessment specific to brain neoplasms. We aim to provide a review of the current use of the EORTC QLQ-BN20 for patients with brain metastases.Materials & methods: All studies utilizing the QLQ-BN20 for QoL assessment in patients receiving treatments related to brain metastases were included. Study information including treatment type, assessment periods, patient enrolment and all information pertaining to the QLQ-BN20 were extracted.Results: A total of 13 studies were identified, five of which were randomized trials assessing prophylactic whole brain radiation for patients with small-cell lung cancer. The QLQ-BN20 was used in conjunction with the core QLQ-C30 questionnaire in all but one of the studies and together these comprised the entire QoL assessments for 11 of the 13 studies. Neurocognitive function assessments supplemented QoL in four studies and accompanying performance status indices used with the QLQ-BN20 varied. Compliance issues were commonly cited. QoL changes during study periods varied as improvements, deteriorations and stabilizations were all observed.Conclusion: QoL assessments should be conducted using disease-specific tools. Future studies should minimize patient burden in order to maximize data collection and accrual. A common set of QoL end points for patients with brain metastases should be created.